2010
DOI: 10.1051/0004-6361/201014395
|View full text |Cite
|
Sign up to set email alerts
|

Radially extended kinematics and stellar populations of the massive ellipticals NGC 1600, NGC 4125, and NGC 7619

Abstract: We present high quality long slit spectra along the major and minor axes out to 1.5-2 R e (14-22 kpc) of three bright elliptical galaxies (NGC 1600, NGC 4125, NGC 7619) obtained at the Hobby-Eberly Telescope (HET). We derive stellar kinematic profiles and Lick/IDS indices (Hβ, Mgb, Fe 5015 , Fe 5270 , Fe 5335 , Fe 5406 ). Moreover, for NGC 4125 we derive gas kinematics and emission line strengths. We model the absorption line strengths using Simple Stellar Populations models that take into account the variatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 95 publications
(169 reference statements)
3
47
0
Order By: Relevance
“…To do this we observed 5 stars from the Lick/IDS library using the same instrumental configuration used for the science objects and derived the offsets between our data and the Lick/IDS system. The comparison of our data with the Lick standard systems can be found in Pu et al (2010 , Fig. 4).…”
Section: R (Arcsec)mentioning
confidence: 85%
“…To do this we observed 5 stars from the Lick/IDS library using the same instrumental configuration used for the science objects and derived the offsets between our data and the Lick/IDS system. The comparison of our data with the Lick standard systems can be found in Pu et al (2010 , Fig. 4).…”
Section: R (Arcsec)mentioning
confidence: 85%
“…In a similar way elliptical galaxy (e.g., Carollo et al 1995;Mehlert et al 2000;Pu et al 2010) and cluster of galaxy velocity dispersion profiles (e.g., Lokas et al 2006), exibits a remarkable flattenings at large radii where a Keplerian falloff would be expected. These deviations, ascribed Based on observations collected at the European Southern Observatory, Chile .…”
Section: Introductionmentioning
confidence: 86%
“…In order to take into account the average age difference between field and cluster passive galaxies (e.g. Thomas et al 2005Thomas et al , 2010, we evolve the gradients of Wu et al (2005) for an additional 2 Gyr with Bruzual & Charlot (2003) SSP models (assuming an age gradient of −0.05 and a metallicity gradient of −0.2 consistent with the literature (La Barbera et al 2005;Wu et al 2005)). The extrapolated value (∇ U−R = −0.20) is very close to the one for local ETGs.…”
Section: Colour Gradients In the Passive Cluster Galaxiesmentioning
confidence: 99%
“…NGC 4889 in Coma cluster Coccato, Gerhard & Arnaboldi 2010) as well as in field ellipticals (e.g. Pu et al 2010). More recent studies have extended the age and metallicity measurements to large radii (∼ 8 − 10R e , for example in La ) and revealed that the outer age or metallicity gradients at 1 − 2R e are distinct from those in the inner region (e.g.…”
Section: Implications and Limitationsmentioning
confidence: 99%